The Effect of Transformational Leadership Style on Employee Performance with Motivation Moderation - Fina Mirri Barlian Isa; Tantri Yanuar Rahmat Syah (Penerbit Kemala Indonesia, 2021)
The study's aims to assess the effect of transformational leadership style on employee performance and determine the influence of motivation on the link between transformational leadership style and employee performance. This is a causal research study that use the cell mean model approach to investigate the average difference between the response variables. The sample technique employed in this experiment was simple random sampling. A total of 120 respondent will be surveyed. The result shows, a transformational leadership style improves employee performance (the first hypothesis does not support) while the group of workers who have a strong transformational leadership style outperforms the group of employees who have a week transformational leadership style, especially for employees with low motivation. Here, the employees with a strong transformational leadership style, who feel strongly motivated have no better performance than employees who feel weak motivation. Thus, an employee who feel strong motivation have greater performance than employees who experience weak motivation, especially for employees with a weak leadership style.